DESIGN OF WASTE HEAT UTILIZATION SYSTEM IN BLOWDOWN PROCESS IN BOILER - Nanda Utama, Rizki
Boiler blowdown is process water discharge from the boiler. The goal is to control the boiler water to the specified parameters, among others, to minimize the scale, corrosion, carryover, and other special problems. Blowdown is also used to remove sediment that is not required in the system as well as the excess pressure in the boiler controller. These deposits are usually caused by contamination of the feedwater, internal chemical precipitates, or exceed the solubility limit of solubility of the salt. As a result some of the boiler water will be discharged (blowdown) and replaced with a new feedwater. Besides using chemical treatment methods to maintain boiler feedwater quality, you can also use a blowdown system continuously and intermittently. The feed water is removed to preserve the quality of the boiler feedwater. The problems that arise due to the continuous blowdown system are the wasted heat energy by the fluid in large quantities without any reutilization of the energy. The heat recovery system from water blowdown will be used for heating feed water before entering the boiler and pre-boiler components using a heat exchanger. This heat recovery system can increase the efficiency of PLTU by 0.042% and fuel savings of Rp155.812.163/month. The cost required for this application is Rp3.013.417.774. The price is the purchase price and the installation of the heat exchanger at the PLTU. The payback from the application of this heat recovery system is 19,3 months